Analisis Model Problem Based Learning Pada Fiqih Puasa Untuk Menumbuhkan Empati Dan Kepedulian Sosial Siswa Madrasah Ibtidaiyah - Fathan Qorib (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study aims to analyse the application of Problem Based Learning (PBL) model on Fiqh Fasting Ramadan material in Madrasah Ibtidaiyah, and how the application can foster students' empathy and social care. The PBL model was chosen because it is believed to develop critical thinking skills, cooperation, and active involvement of students in solving problems that are contextual to everyday life. The research method used was descriptive qualitative with a field research approach, through observation, interviews, and documentation at MI Al Mursyidiyyah Pamulang. The results showed that the application of PBL in Fiqh lessons, especially in fasting material, was effective in helping students understand the values of worship as well as bringing up empathetic attitudes towards others, such as sharing iftar food and helping friends in difficulty. Although there were some obstacles such as time constraints and different levels of student participation in discussions, overall PBL was able to improve students' understanding of the concept of fasting in an applicable manner and encourage the formation of social character. These findings reinforce the importance of innovating problem-based learning models in religious education to strengthen affective and spiritual values.